The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1046/j.1365-2265.2000.00975.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of relationship between 11β‐hydroxysteroid dehydrogenase setpoint and insulin sensitivity in the basal state and after 24h of insulin infusion in healthy subjects and type 2 diabetic patients*

Abstract: The present study does not support the hypothesis that insulin resistance in type 2 diabetes mellitus is associated with an overall change in the 11betaHSD set point towards cortisol. In view of the stimulatory effects of insulin and cortisol on adipogenesis, long-term stimulation of 11betaHSD reductase activity by insulin could aggravate visceral obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 49 publications
(55 reference statements)
0
31
0
Order By: Relevance
“…Kerstens et al (15) reported an increase in urinary free cortisol and cortisone, as well as of urinary metabolites of cortisol, without any changes of plasma cortisol and cortisone, in healthy men submitted to a 24 h low-dose hyperinsulinaemic clamp. Interestingly, no change was observed in insulinresistant type 2 diabetic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Kerstens et al (15) reported an increase in urinary free cortisol and cortisone, as well as of urinary metabolites of cortisol, without any changes of plasma cortisol and cortisone, in healthy men submitted to a 24 h low-dose hyperinsulinaemic clamp. Interestingly, no change was observed in insulinresistant type 2 diabetic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…[59,60,61]) and might explain the association of low birth weight and insulin resistance [62]. Alterations in cortisol excretion and HPA axis regulation have specifically been observed in diabetes mellitus [63,64,65,66,67]. A recent study involving moderately overweight Type 2 diabetic patients and control subjects matched for weight, height, BMI and blood pressure showed increased central and peripheral sensitivity to glucocorticoids in diabetic patients even if their metabolism was optimally controlled (HbA 1c 6.9±0.2% vs 6.0±0.1%) [68].…”
Section: β-Hsd1 and Insulin Resistancementioning
confidence: 99%
“…The conventional measure of 11HSD1 is the ratio of urinary cortisol to cortisone metabolites, which is inconsistently altered in obesity (11)(12)(13)(14)(15)(16) and diabetes (17)(18)(19). However, this ratio may be confounded by the activity of other enzymes (e.g., 11HSD type 2, 5␣-and 5␤-reductase) that differ in obesity, and is insensitive to the tissue-specific changes in 11HSD1 that have been observed in animals.…”
mentioning
confidence: 99%